A 24-hour interval compression plan for managing chronic oedema: part 1—the science and theory behind the concept. (1st February 2022) - Bock, Karen J; Muldoon, Jeanette
Abstract : Compression, skin care, manual lymph drainage and exercise form the mainstays of treatment of chronic limb oedema. The compression aspect of the regimen is often prescribed and used without conscious concern for the patient's ability for self-adjustment and skin hygiene. This article will focus on the action of compression therapy using a new concept of encouraging patients to apply and reapply an adjustable compression garment or multiple garment types during a 24-hour interval. The benefits of this focus on interval compression therapy on all aspects of care will be explained and case studies presented.